2018
DOI: 10.1080/02699931.2018.1434132
|View full text |Cite
|
Sign up to set email alerts
|

Conflict-driven adaptive control is enhanced by integral negative emotion on a short time scale

Abstract: Negative emotion influences cognitive control, and more specifically conflict adaptation. However, discrepant results have often been reported in the literature. In this study, we broke down negative emotion into integral and incidental components using a modern motivation-based framework, and assessed whether the former could change conflict adaptation. In the first experiment, we manipulated the duration of the inter-trial-interval (ITI) to assess the actual time-scale of this effect. Integral negative emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 72 publications
6
34
1
Order By: Relevance
“…On a very speculative note, the absence of conflict effects in Experiment 3 might point to the possibility that the presence of performance feedback is an important boundary condition to observe conflict-driven modulation of the corrugator muscle. It should be noted that errors were not punished in the present research-unlike in other experiments where errors sometimes lead to loss of points or feedback is provided by unpleasant auditory or sensory signals (e.g., Lindström et al, 2013;Yang & Pourtois, 2018). Interestingly, the magnitudes of the conflict-adaptation effect in Experiment 3 and Experiment 2 were comparable (see the confidence intervals reported in Table 1), suggesting that the conflict adaptation can happen in the absence of aversive signals detectable with EMG.…”
Section: Discussioncontrasting
confidence: 61%
“…On a very speculative note, the absence of conflict effects in Experiment 3 might point to the possibility that the presence of performance feedback is an important boundary condition to observe conflict-driven modulation of the corrugator muscle. It should be noted that errors were not punished in the present research-unlike in other experiments where errors sometimes lead to loss of points or feedback is provided by unpleasant auditory or sensory signals (e.g., Lindström et al, 2013;Yang & Pourtois, 2018). Interestingly, the magnitudes of the conflict-adaptation effect in Experiment 3 and Experiment 2 were comparable (see the confidence intervals reported in Table 1), suggesting that the conflict adaptation can happen in the absence of aversive signals detectable with EMG.…”
Section: Discussioncontrasting
confidence: 61%
“…It was found previously that conflict is inherently aversive and thus negatively connoted (Dreisbach & Fischer, 2012). Recently, we also found that the CSE was increased during the encounter of integral negative emotion (Yang & Pourtois, 2018). Negative emotion might provide another source triggering enhanced control adjustments, given the close ties between 7 defensive motivation and CC (Inzlicht et al, 2015).…”
Section: Introductionsupporting
confidence: 53%
“…Based on the evidence reviewed here above, we reasoned that evaluative feedback should have different impacts on the CSE depending on conflict frequency. More specifically, evaluative feedback (with a higher motivational significance) should strengthen reactive control when conflict frequency is low, thereby increasing the CSE (see also Van Steenbergen, Band, & Hommel, 2009Yang & Pourtois, 2018). By comparison, this increase in the size of the CSE should not be observed when conflict frequency is high and thus proactive control presumably dominates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations